2007
DOI: 10.1136/bjsm.2006.032730
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-actin in muscle damage of injured athletes in comparison with traditional markers

Abstract: Objective: In order to identify a reliable marker for the early detection of muscle injuries in sports, a-actin protein and other markers of muscle damage were studied in sera of uninjured sportspeople and those with skeletal muscle injury. Methods: Blood samples were obtained from 20 sportspeople with skeletal muscle injury and 48 uninjured sportspeople. Immunoassays were performed to determine cardiac troponin I (TnI), troponin T, lactate dehydrogenase and myoglobin concentrations. Western blot and densitome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…More research is needed to determine the real diagnostic and prognostic value of potential markers, such as ‘fast myosin heavy chains’ (fast MHC) [26], ‘skeletal-troponin I’ (sTnI) [55] and ‘alfa-actin’ [40]. …”
Section: Resultsmentioning
confidence: 99%
“…More research is needed to determine the real diagnostic and prognostic value of potential markers, such as ‘fast myosin heavy chains’ (fast MHC) [26], ‘skeletal-troponin I’ (sTnI) [55] and ‘alfa-actin’ [40]. …”
Section: Resultsmentioning
confidence: 99%
“…An altered Acta1 gene expression associated with the loss of contractile muscle mass was observed by other groups investigating degeneration in human rotator cuff muscles . Moreover, the release of Acta1 into the blood stream after skeletal muscle damage has been observed in animals and humans .…”
Section: Discussionmentioning
confidence: 59%
“…Amat et al (2007) described earlier that only muscle trauma or lesions caused major actin release into the circulation, so it is possible that plasma actin might be useful for the distinction between micro injuries as well as severe muscle damages and lesions. Supporting this idea, we did not detect any relationship between the plasma actin level and CK or the muscle soreness score.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Amat et al (2007) found higher α -actin levels in athletes with skeletal muscle lesions versus healthy athletes, suggesting that α -actin concentration might be sensitive to EIMD in athletes. In contrast, Féasson et al (2002) reported that the amount of α -actin remained unchanged immediately, 1 and 14 days after downhill treadmill running.…”
Section: Introductionmentioning
confidence: 98%